1984
DOI: 10.1111/j.1438-8677.1984.tb01795.x
|View full text |Cite
|
Sign up to set email alerts
|

Theil's Inequality Index Applied to Quantify Population Variation of Plants With Regard to Dry Matter Allocation

Abstract: The inequality index ofTHEIL (1967) was initially developed to calculate income inequality in human populations. It is applied here to determine the per organ dry weight variation in plant populations and integrated to an index of population variation (lPV). The weight fractions used to calculate the IPV are further used to calculate an allocation index (AI) for each plant member of a population. The method implicates the possibility to reconstruct the relative contribution of each organ (or individual) to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Later, when competition for light develops, dominance and suppression occur. The results of Andel et al (1984) on Urtica dioica are illuminating in this context. They compared inequality in individually grown and competing individuals at five harvest dates.…”
Section: Density and Size Inequalitymentioning
confidence: 95%
“…Later, when competition for light develops, dominance and suppression occur. The results of Andel et al (1984) on Urtica dioica are illuminating in this context. They compared inequality in individually grown and competing individuals at five harvest dates.…”
Section: Density and Size Inequalitymentioning
confidence: 95%
“…4). Schmitt et al (1987b) also found less inequality late as compared to early in the season in thinned plots of Impatiens capensis, though in this instance greater mortality among smaller plants may have contributed to the decline (see also Hara 1984b for Helianthus annuus, van Andel et al 1984 for Urtica dioica under non-competitive conditions). It follows then that size inequality will not increase indefinitely but instead will level off or even decline in mature stands (Weiner and Thomas 1986), barring strong competition.…”
Section: Plant Development Size-specific Growth Rates and Size Ineqmentioning
confidence: 98%
“…This was true of control and low-density plantings of P. arenastrum. Schmitt et al (1987b) also found less inequality late as compared to early in the season in thinned plots of Impatiens capensis, though in this instance greater mortality among smaller plants may have contributed to the decline (see also Hara 1984b for Helianthus annuus, van Andel et al 1984 for Urtica dioica under non-competitive conditions). In effect, size differences that are built up during periods of accelerated growth disappear as plants "catch up to each other," unless other factors such as competition intervene to limit the ability of smaller plants to grow to a larger size.…”
Section: Planting Densitymentioning
confidence: 98%
“…In some cases, it will not matter which framework one uses for looking at inequality. For example, all measures of inequality, such as the Gini coefficient, the coefficient of variation, Theil's measure of entropy (van Andel et al 1984), or the standard deviation of the logtransformed distribution, will tend to be correlated. If one is just asking if a specific factor or treatment will increase or decrease inequality, then the interpretation of the data will probably not be affected by which framework the researcher takes.…”
Section: Discussionmentioning
confidence: 99%